2021
DOI: 10.1108/prt-06-2021-0064
|View full text |Cite
|
Sign up to set email alerts
|

The effects of coating colours on base papers

Abstract: Purpose The purpose of this paper is to investigate the influences of coating colours and their contents on the fundamental properties of base papers and also evaluate these results in terms of mechanical and wood-free papers. Design/methodology/approach A design research approach has been based on the application of various coating colours and analysis of mechanical and optical tests results of the coated mechanical and wood-free base papers. Findings This study is confirmed that the coating colours can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This should be taken into account when assessing the suitability of WTT papers for printing and other applications. However, previous studies have shown that WTT papers with coated suspension, including GCC, have printability-acceptable surface strength wax numbers. Filler materials like GCC can reduce paper surface strength, but this may not always affect print quality. Studies suggest that the optimal surface strength wax number for printability depends on the printing method, ink type, and paper properties.…”
Section: Resultsmentioning
confidence: 99%
“…This should be taken into account when assessing the suitability of WTT papers for printing and other applications. However, previous studies have shown that WTT papers with coated suspension, including GCC, have printability-acceptable surface strength wax numbers. Filler materials like GCC can reduce paper surface strength, but this may not always affect print quality. Studies suggest that the optimal surface strength wax number for printability depends on the printing method, ink type, and paper properties.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been conducted on the effect of recycling on the physical and optical properties of paper (Atik, 1999; Tze and Gardner, 2001; Vahey et al , 2006; Husovska et al , 2015; Engin et al , 2021; Hu et al , 2017). According to the results of the study, it is determined that the number of recycling decreased the opacity of the paper and increased its whiteness and yellowness.…”
Section: Discussionmentioning
confidence: 99%
“…Only the proportion of PCC and GCC was chosen as a variable (25%, 50%, 75% and 100%), while the amount of the components (water, starch and CMC) in the coating colors was kept constant. It is well known that the pigment particle size and the distribution within the coating color play an important role in achieving the desired optical and physical qualities of paper (Engin et al , 2021; Murray and Kogel, 2005). The particle size of PCC and GCC should be 2–3 µm or smaller to get a suitable degree of dispersion of pigments within color.…”
Section: Methodsmentioning
confidence: 99%